Pembuatan Bahan Ajar E-Learning Post Pandemic dengan Software Filmora X - Sri Endang Wahyuni; Puji Suharmanto (UNIVERSITAS INDRAPRASTA PGRI, 2022)
The learning process in the post-pandemic era still relies on digital technology called e-learning. This shows that the need for e-learning teaching materials is still in great demand. This research is motivated by teachers who are members of the Physics Subject Teacher Conference (MGMP) in Karawang Regency, requiring training on several learning media updates, especially learning videos that are deemed appropriate as e-learning teaching materials that are digital and flexible so that they support the e-learning process. effective and efficient learning. Therefore, the Abdimas Team carried out a program that aims to improve the ability of teachers in compiling materials, recording themselves, editing videos and utilizing Filmora X software into physics learning videos. The methods used in the implementation of this program are training, discussion and mentoring. Based on the results of the questionnaire, after 3 days the participants took part in the teacher's ability and knowledge training increased by 80% and there was a positive response in making learning videos using Filmora X software.